2012
DOI: 10.1590/s1676-24442012000100011
|View full text |Cite
|
Sign up to set email alerts
|

A necessidade da imunofluorescência direta no diagnóstico da dermatose bolhosa por IgA

Abstract: A dermatose bolhosa por imunoglobulina da classe A linear (DbIgA) do adulto é uma doença autoimune rara caracterizada por formação de bolhas subepidérmicas e depósito linear de imunoglobulina da classe A (IgA) na zona da membrana basal (ZMB). Por possuir aspectos clínicos e histológicos semelhantes a outras dermatoses bolhosas, principalmente a dermatite herpetiforme e o penfigoide bolhoso, faz-se necessária a realização de imunofluorescência direta para confirmação diagnóstica. Apresenta-se então, neste artig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, others have been reported, such as collagen VII, bullous pemphigoid 230 kDa antigen, and laminina. 7 The term linear IgA and IgG dermatosis (LAGD) is proposed for a subtype or variant of the disease that occurs with deposition of both immunoglobulins and that is found more in adults than in children. 7 A study of four patients with IgA and IgG deposition in the BMZ concluded that the clinical and histopathological findings, as well as the target-antigen (97 kDa extracellular domain of BP 180), were similar to patients with LAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others have been reported, such as collagen VII, bullous pemphigoid 230 kDa antigen, and laminina. 7 The term linear IgA and IgG dermatosis (LAGD) is proposed for a subtype or variant of the disease that occurs with deposition of both immunoglobulins and that is found more in adults than in children. 7 A study of four patients with IgA and IgG deposition in the BMZ concluded that the clinical and histopathological findings, as well as the target-antigen (97 kDa extracellular domain of BP 180), were similar to patients with LAD.…”
Section: Discussionmentioning
confidence: 99%
“… 7 The term linear IgA and IgG dermatosis (LAGD) is proposed for a subtype or variant of the disease that occurs with deposition of both immunoglobulins and that is found more in adults than in children. 7 A study of four patients with IgA and IgG deposition in the BMZ concluded that the clinical and histopathological findings, as well as the target-antigen (97 kDa extracellular domain of BP 180), were similar to patients with LAD. 8 For some authors, LAGD and childhood LAD share similar characteristics and are manifested as a bullous, pruritic rash.…”
Section: Discussionmentioning
confidence: 99%